KAJIAN KOMPOSISI SERANGGA POLINATOR PADA TUMBUHAN PENUTUP TANAH DI PONCOKUSUMO – MALANG - Budi Purwantiningsih; Amin Setyo Leksono; Bagyo Yanuwiadi (The East Java Biological Society, 2012)
The use of pesticides on agricultural land has a negative impact on health, economic, and environment. The using of variety of ground cover plants as refugia area are expected to be an alternative habitat for pollinators insect in plants: Cyperus rotundus L., Bidens pilosa L., Commelina difussa L., Capsicum frutescens L., and Ageratum conyzoides L. Observations made by